Waste lithium battery electrode recycling and regenerating method

Through two-step acid leaching method and antioxidant treatment, impurity ions were successfully removed, and a lithium manganese ferrophosphate electrode material with divalent iron and manganese was directly prepared, solving the problems of complex processes and high impurity content in the existing technology, and improving the Properties and purity of electrode materials.

CN119153830APending Publication Date: 2024-12-17JIANGSU BTR NANO TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411004392.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-25
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

In the prior art, when recycling waste lithium batteries, it is difficult to directly use non-oxidized forms to remove impurities and ions, resulting in complex process flow and high impurities content, which affects the purity and performance of lithium manganese iron phosphate electrode materials.

Method used

Using two-step acid leaching method and antioxidant treatment, iron powder is added by metering copper ions in the acid leaching solution, adjusting the pH value, and adding manganese composition after filtration to increase the temperature, so that the ferrous ions are precipitated in the form of lithium manganese iron phosphate combined salt, combined with By beating and sintering steps, lithium manganese iron phosphate electrode materials of divalent iron and manganese are prepared.

Benefits of technology

Shorten the process flow, remove impurities and ions, improve the purity and performance of the electrode material, reduce the complexity of post-treatment, realize the preparation of divalent iron and manganese under normal pressure, improve the uniformity of the electrode material and electric potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153830A_ABST
    Figure CN119153830A_ABST
Patent Text Reader

Abstract

The invention discloses a waste lithium battery electrode recycling and regenerating method which comprises the following steps: (1) crushing a waste lithium battery electrode and carrying out acid leaching with sulfuric acid, hydrochloric acid or phosphoric acid to obtain an acid leaching solution; (2) adding 1.2-2.0 equivalent weight of iron powder into the pickle liquor according to the molar weight of copper ions in the pickle liquor under the protection of inert gas, reacting for not less than 30 minutes, adjusting the pH value to 1.5-2.0 by using ammonia water, and filtering to obtain a first impurity-removed solution; (3) adding not less than 0.05% of an antioxidant into the first impurity-removed solution by mass, adjusting the pH value to 2.6-3.5 by using ammonia water, and filtering to obtain a second impurity-removed solution; and (4) adding a manganese-containing composition into the second impurity-removed solution, and heating to 90-100 DEG C, so that ferrous ions are separated out in the form of lithium manganese iron phosphate double salt, and the precipitate is the regenerated electrode material. Impurities in the electrode are removed and recycled in a non-oxidation mode, the technological process is shortened, high-temperature and high-pressure conditions are not needed, and the preparation process is milder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a phosphate synthesis method, in particular to a waste lithium battery electrode recovery and regeneration method. Background Art

[0002] Recycling retired lithium batteries can ease resource pressure, reduce production costs, and facilitate resource recycling and environmental protection. The wet recycling process is a commonly used recycling process in engineering because of its high recovery rate of valuable metals, high product purity, low energy consumption in the recycling process, and less environmental pollution. The first step in wet recycling of lithium batteries is acid leaching, which is to use acid to transfer the metal in the positive electrode material into the leachate. The composition of lithium batteries also includes binders, electrolytes, diaphragms, shells, covers, etc. During recycling, the positive and negative electrodes will inevitably carry metal or non-metallic impurities. Among them, metal impurities are mainly filtered metals such as copper and aluminum. During acid leaching, metal impurities enter the leachate in the form of ions. Therefore, the removal of these impurity ions needs to be considered during the recycling process.

[0003] The invention patent application with the publication number CN118026126A discloses a method for recovering iron phosphate from waste ferrophosphorus slag, which uses a two-step acid leaching method to reduce the impurity ions contained in the leachate, remove copper ions with iron powder, and oxidize ferrous iron to remove aluminum ions by early precipitation of iron phosphate. The aluminum ions are removed by oxidation, and aluminum is easily wrapped by iron phosphate, so the precipitation of iron phosphate is incomplete, the recovery is not thorough, and the impurity content is high. The invention patent application with the publication number CN111009660A discloses a method for preparing lithium iron phosphate positive electrode materials from waste lithium iron phosphate batteries. In this scheme, impurity ions can be removed, but inevitably ferrous phosphate needs to be oxidized to iron phosphate before it can be recovered. After the iron phosphate is aged and recovered, a large amount of carbon source still needs to be added to reduce it to lithium iron phosphate before it can be put into use. The invention patent application with publication number CN117458025A discloses a combined lithium battery recovery method. In this scheme, iron phosphate is also recovered by oxidation, but the impurity ions in the leachate are removed in advance to ensure the purity of the iron phosphate. On the one hand, lithium hydroxide is used to recover iron phosphate, and further recovery of lithium requires additional steps. On the other hand, other ions are introduced into the leachate, and ferrous phosphate cannot be used under direct liquid phase conditions.

[0004] As a positive electrode material for lithium batteries, lithium manganese iron phosphate (LMFP) has become a material of great concern in the field of new energy due to its advantages such as high performance, stability and economy. LMFP synthesized by liquid phase method has more uniform mixing at the molecular level, and the size and morphology of the product are controllable. How to directly use recycled lithium iron materials to prepare lithium manganese iron phosphate (LMFP) is a problem that needs to be solved. Summary of the invention

[0005] Purpose of the invention: The purpose of the present invention is to provide a method for recycling waste lithium battery electrodes, which can remove impurities in the recycled electrodes in a non-oxidative form and shorten the process flow.

[0006] Technical solution: The method for recycling and regenerating waste lithium battery electrodes of the present invention comprises the following steps:

[0007] (1) crushing the waste lithium battery electrodes and leaching them with sulfuric acid, hydrochloric acid or phosphoric acid to obtain an acid leaching solution;

[0008] (2) under the protection of inert gas, 1.2 to 2.0 equivalents of iron powder are added to the acid leaching solution based on the molar amount of copper ions in the acid leaching solution, reacting for not less than 30 minutes, adjusting the pH to pH = 1.5 to 2.0 with ammonia water, filtering, and obtaining a first impurity removal solution;

[0009] (3) adding not less than 0.05% by mass of an antioxidant to the first impurity-removing solution, adjusting the pH to pH=2.6-3.5 with aqueous ammonia, and filtering to obtain a second impurity-removing solution;

[0010] (4) Adding a manganese-containing composition to the second impurity-removing solution and heating it to 90-100° C., precipitating ferrous ions in the form of lithium manganese iron phosphate complex salt, and the precipitate is the regenerated electrode material.

[0011] The manganese and iron in the regenerated lithium manganese iron phosphate electrode obtained by the present invention are both divalent and do not need to be further reduced.

[0012] Preferably, in step (1), the concentration of sulfuric acid, hydrochloric acid or phosphoric acid is 2.5-3.0 mol / L, the solid-liquid ratio of acid leaching is 1:2.5-3, the temperature is 60-75°C, and the duration of acid leaching is not less than 1.5 hours. The lower the acid leaching temperature, the longer the leaching time needs to be.

[0013] Preferably, in step (2) and step (3), the mass fraction of aqueous ammonia is 10-15%, and the impurity removal rate and yield are guaranteed within this range.

[0014] Preferably, in step (3), not less than 0.1% of an antioxidant is added, and ammonia water is used to adjust the pH to 2.8-3.5 to ensure the aluminum ion removal rate and yield.

[0015] Preferably, in step (3), the antioxidant is a water-soluble organic antioxidant and / or an inorganic antioxidant.

[0016] Preferably, in step (3), the organic antioxidant is at least one of ascorbic acid and sodium ascorbate, and the inorganic antioxidant is at least one of sodium thiosulfate, sodium sulfite and sodium bisulfite.

[0017] Preferably, in step (4), the temperature is raised to 95-100°C, the reaction is carried out for not less than 4 hours, and the solid is filtered to obtain the regenerated electrode material. The electrode material can be obtained by heating under normal pressure and an open system.

[0018] Preferably, in step (4), the manganese-containing composition is a manganese source, a lithium source, or a lithium source composition, and the manganese-containing composition is added to the second impurity-removing solution so that the molar ratio of lithium: manganese: iron: phosphorus in the second impurity-removing solution is 1.5:0.6-0.7. The ratio of manganese to iron is controlled to ensure the electrode and capacitor performance of the material.

[0019] Preferably, the manganese source is at least one of manganous sulfate, manganous nitrate, manganous chloride and manganous acetate, the lithium source is at least one of lithium carbonate, lithium hydroxide, lithium acetate and lithium nitrate, and the phosphorus source is at least one of phosphoric acid, ammonium dihydrogen phosphate and diammonium hydrogen phosphate.

[0020] Preferably, the step (4) further comprises a step of impurity removal and drying, wherein the impurity removal step comprises: pulping and washing the regenerated electrode material with deionized water at 60 to 70° C. The pulping is used to remove sulfate introduced by the acid leaching or secondary impurity removal step.

[0021] Preferably, the step (4) further comprises a sintering and crushing step: the obtained regenerated electrode material is mixed with a carbon source, sintered at 500-600°C for 2-4 hours, and crushed, and the particle size after crushing does not exceed 10 μm, and the carbon source is one or more of cyclodextrin, glucose, graphene, carbon nanotubes, fullerene, sucrose, starch, PEG, PVP, and citric acid. The sintering time can be shortened by increasing the sintering temperature.

[0022] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: 1. The process flow is shortened and the reaction conditions are mild: through two-step impurity removal, the impurity ions Ti, Cu, and Al contained in the acid leaching solution are fully removed, and there is no need to introduce additional impurity removal agents such as sodium fluoride or sodium sulfide, which helps to reduce post-processing; the obtained electrode material exists in the form of divalent iron in the liquid phase, and solid electrode materials can be obtained by mixing and heating with manganous salts under normal pressure and an open system, without the need for high pressure, gas protection, etc., and the preparation process is safer; 2. The impurity content meets the standard: after the two-step impurity removal, the copper ion content of the solution is less than 3ppm, and the content of other impurity ions is less than 50ppm; 3. The post-processing is simple: other ions introduced for impurity removal can be removed in the pulping and washing step; 4. The performance of the electrode material is improved: the divalent iron is directly present in the liquid phase, and the electrode material is directly prepared from the liquid phase. The size and morphology of the product are controllable, which can improve the uniformity of the electrode material and help to improve the compaction density; 5. Improve the electrode potential: divalent manganese can be directly introduced into the recycled material, which helps to improve the potential of the recycled electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a flow chart of the steps of recovering ferrous phosphate and preparing lithium iron manganese phosphate of the present invention;

[0024] Figure 2 This is a 100,000-fold magnified SEM image of the lithium manganese iron phosphate synthesized in the liquid phase of the present invention;

[0025] Figure 3 The figure is the XRD diagram of the final product lithium iron manganese phosphate prepared by the present invention. DETAILED DESCRIPTION

[0026] The technical solution of the present invention is further described below in conjunction with the accompanying drawings. Unless otherwise specified, the reagents used in the following examples are all commercially available analytically pure reagents and are used directly without further purification.

[0027] Example 1: Recovery of ferrous phosphate and preparation of lithium iron manganese phosphate

[0028] 1. Raw materials: The waste lithium iron phosphate electrode sheets that have been disassembled after discharge are soaked in hot water to peel off the positive electrode active material and the current collector. The positive electrode active material is then dried and ground to obtain the waste lithium iron phosphate positive electrode material. The main component of the recovered positive electrode material is lithium iron phosphate. The content of each element is determined by inductively coupled plasma optical emission spectrometry (ICP-OES). The results are shown in Table 1.

[0029] Table 1: ICP analysis results of positive electrode materials

[0030] category Fe / % Li% P / % Al / ppm Cu / ppm Ti / ppm Mn / ppm Mg / ppm content 24.79 4.5 13.75 12008 3656 1897 2543 121

[0031] 2. Ferrous phosphate recovery

[0032] (1) Acid leaching: Under the protection of an inert gas atmosphere such as nitrogen, a 3 mol / L dilute sulfuric acid solution is added to the lithium iron phosphate pre-treated slag, the solid-liquid ratio is controlled to be 1:3, the reaction temperature is controlled at about 70°C, and the reaction time is about 1.5 h. After the reaction is completed, the solution is filtered and the filter cake is washed with a low concentration of H2SO4 with a mass fraction of 0.5%-1%. The pH of the low concentration of H2SO4 is controlled within 2.0 to replace the leachate contained in the filter cake and improve the leaching rate.

[0033] (2) First impurity removal: Add iron powder to the filtrate of step (1), with the molar ratio of iron powder to copper ions in the solution being 2:1. After reacting at room temperature for about 30 minutes, adjust the pH to 1.5 using 12% ammonia water, quickly filter the liquid, and retain the filtrate.

[0034] (3) Second impurity removal: Add antioxidant ascorbic acid to the filtrate of step (2) in an amount of 0.1% of the mass of the filtrate, slowly adjust the pH to 3.2 using 12% ammonia water at room temperature, filter the solution, and obtain a ferrous phosphate impurity removal solution.

[0035] The ion content in the obtained solution was detected by ICP-OES method, and the content of each element is shown in Table 2.

[0036] Table 2: Analysis results of ferrous phosphate impurity removal solution

[0037] category Al / ppm Cu / ppm Ti / ppm Mg / ppm content 40 2.4 56 153 Reference Standards <50ppm <3ppm <100ppm <200ppm

[0038] 3. Preparation of lithium iron manganese phosphate electrode materials

[0039] (1) Without gas protection, manganese sulfate, phosphoric acid and lithium carbonate are added to the ferrous phosphate impurity removal solution, and the molar ratio of lithium: manganese: iron: phosphorus in the solution is controlled to be 1.5:0.6:0.4:1.0, the pH range is about 1.5, the reaction temperature is about 100°C, and the reaction time is not less than 4 hours. After the reaction, the reaction liquid is filtered, the filter cake is taken, and it is pulped and washed twice with deionized water at about 60-70°C.

[0040] (2) The obtained filter cake is flash-evaporated and dehydrated, and then sintered at a sintering temperature of 500° C. The sintering time is controlled to be about 4 hours. After sintering, the lithium iron manganese phosphate precursor is crushed. The obtained lithium iron manganese phosphate precursor has the structure as shown below: Figure 2 As shown, the particle size is uniform. Based on the iron content, the iron recovery rate is 95-97%.

[0041] (3) Detect the lithium content in the obtained lithium iron manganese phosphate precursor, and determine whether lithium carbonate needs to be added to the obtained powder according to the standard to maintain the molar ratio of lithium: manganese: iron: phosphorus = 1.1: 0.6: 0.4: 1.0, add 5% glucose and 4% sucrose of the total powder mass, 4.5% polyethylene glycol of the total powder mass, sand grind for 30 minutes and then spray dry, sinter at 700 ° C for 12 hours under nitrogen atmosphere, and obtain lithium iron manganese phosphate material. XRD test is performed on the obtained material. The test results are shown in Figure 3 , compared with the standard lithium iron manganese phosphate spectrum, the peak shape and position are consistent, indicating that the obtained material is lithium iron manganese phosphate.

[0042] 4. Preparation of iron phosphate electrode materials

[0043] Without gas protection, the ferrous ion content in the ferrous phosphate impurity removal solution is detected, and an excess amount (0.55-0.6 equivalent) of hydrogen peroxide is added based on the molar amount of ferrous ions, the pH is adjusted to 2.0, the temperature is raised to 65°C, the reaction is carried out for more than 2 hours, the reaction is aged, filtered, and the solid is taken. The obtained material is ferric phosphate.

[0044] Example 2: First impurity removal of pickling liquid

[0045] In this embodiment, the raw materials used are consistent with those in Example 1, and the ferrous phosphate recovery step is similar to that in Example 1, except that the experimental parameters of step (2) are adjusted, and the quality of the obtained ferrous phosphate impurity-removing solution is tested. Different experimental conditions and test results are shown in Table 3.

[0046] Table 3: Analysis results of ferrous phosphate impurity removal solution

[0047]

[0048] The data show that the pH is too high and the impurity ion content in the solution exceeds the standard. During the first impurity removal process, the pH is preferably 1.5-2.0 and the iron powder is about 1.2 equivalents. When the ammonia water is replaced with other alkalis, such as NaOH, the precipitation speed is too fast and the effect is not good.

[0049] Example 3: Second impurity removal of pickling liquid

[0050] In this embodiment, the raw materials used are consistent with those in Example 1, and the ferrous phosphate recovery step is similar to that in Example 1, except that the experimental parameters of step (3) are adjusted, and the quality of the obtained ferrous phosphate impurity-removing solution is tested. Different experimental conditions and test results are shown in Table 4.

[0051] Table 4: Analysis results of ferrous phosphate impurity removal solution

[0052]

[0053] The data show that when pH=2.5, the impurity content is close to the critical value, and the pH is preferably higher than 2.5. The experiment found that the mass fraction of ammonia water used to adjust the pH is preferably 10-15%. When it is lower than 10%, the solid content of the solution system decreases, and the difficulty of the impurity removal process increases. When it is higher than 15% or the end point pH is higher than 3.5, it is beneficial to remove impurity ions, but the yield is easy to be lower than 90%. The purpose of adding an antioxidant is to prevent the oxidation of ferrous ions into ferric ions during the aluminum removal process and precipitate in the form of ferric phosphate. The experiment also found that adding an antioxidant in step (3) is beneficial to maintaining the iron recovery rate, while adding an equal amount of antioxidant in the acid leaching or the first impurity removal step has no such effect.

[0054] Example 4: Performance test of lithium manganese iron phosphate electrode

[0055] The performance test of the lithium iron manganese phosphate electrode material prepared in Examples 1 to 3 is performed, and the test results are shown in Table 5. The test parameters and methods are as follows: the Xinwei test system uses constant current-constant voltage charging (CC-CV) and constant current discharge (DC) test methods to test and analyze the charge and discharge behavior of the button battery; the compaction density test is performed according to GBT30835-2014, and the PRCD1100 powder is used to compact the material to be tested.

[0056] Table 5:

[0057]

[0058] The data show that this scheme can effectively recover the metal ions of lithium iron phosphate electrode and keep the compaction density of the obtained lithium iron manganese phosphate electrode material at 2.20g / cm 3 The 0.1C discharge specific capacity is maintained at around 160mAh / g, and after 500 cycles of 0.1C charge and discharge, the capacity retention rate is maintained at around 90%.

Claims

1. A method for recycling waste lithium battery electrodes, It is characterized in that The following steps are involved: (1) crushing the waste lithium battery electrodes and leaching them with sulfuric acid, hydrochloric acid or phosphoric acid to obtain an acid leaching solution; (2) under the protection of inert gas, 1.2 to 2.0 equivalents of iron powder are added to the acid leaching solution based on the molar amount of copper ions in the acid leaching solution, reacting for not less than 30 minutes, adjusting the pH to pH = 1.5 to 2.0 with ammonia water, filtering, and obtaining a first impurity removal solution; (3) adding not less than 0.05% by mass of an antioxidant to the first impurity-removing solution, adjusting the pH to pH=2.6-3.5 with aqueous ammonia, and filtering to obtain a second impurity-removing solution; (4) Adding a manganese-containing composition to the second impurity-removing solution, heating it to 90-100° C., precipitating ferrous ions in the form of lithium manganese iron phosphate complex salt, and the precipitate is the regenerated electrode material.

2. The method for recycling waste lithium battery electrodes according to claim 1, It is characterized in that In the step (1), the concentration of sulfuric acid, hydrochloric acid or phosphoric acid is 2.5-3.0 mol / L, the solid-liquid ratio of acid leaching is 1:2.5-3, the temperature is 60-75° C., and the duration of acid leaching is not less than 1.5 hours.

3. The method for recycling waste lithium battery electrodes according to claim 1, It is characterized in that In the steps (2) and (3), the mass fraction of aqueous ammonia is 10 to 15%.

4. The method for recycling waste lithium battery electrodes according to claim 1, It is characterized in that In the step (3), no less than 0.1% of an antioxidant is added to the first impurity removal solution, and ammonia water is used to adjust the pH to 2.8-3.

5.

5. The method for recycling waste lithium battery electrodes according to claim 1, It is characterized in that In step (3), the antioxidant is a water-soluble organic antioxidant and / or an inorganic antioxidant, the organic antioxidant is at least one of ascorbic acid and sodium ascorbate, and the inorganic antioxidant is at least one of sodium thiosulfate, sodium sulfite, and sodium bisulfite.

6. The method for recycling waste lithium battery electrodes according to any one of claims 1 to 5, It is characterized in that In step (4), the temperature is raised to 95-100° C., the reaction is carried out for not less than 4 hours, and the solid is filtered to obtain a regenerated electrode material.

7. The method for recycling waste lithium battery electrodes according to any one of claims 1 to 5, It is characterized in that In step (4), the manganese-containing composition is a manganese source, a lithium source, or a lithium source composition. The manganese-containing composition is added to the second impurity-removing solution so that the molar ratio of lithium: manganese: iron: phosphorus in the second impurity-removing solution is 1.5:0.6-0.7:0.4-0.3:1.

0.

8. The method for recycling waste lithium battery electrodes according to claim 7, It is characterized in that The manganese source is at least one of manganous sulfate, manganous nitrate, manganous chloride and manganous acetate; the lithium source is at least one of lithium carbonate, lithium hydroxide, lithium acetate and lithium nitrate; and the phosphorus source is at least one of phosphoric acid, ammonium dihydrogen phosphate and diammonium hydrogen phosphate.

9. The method for recycling waste lithium battery electrodes according to claim 7, It is characterized in that The step (4) also includes impurity removal and drying steps, wherein the impurity removal step is to use deionized water at 60 to 70° C. to pulp and wash the regenerated electrode material.

10. The method for recycling waste lithium battery electrodes according to claim 9, It is characterized in that The step (4) also includes a sintering and crushing step: the obtained regenerated electrode material is mixed with a carbon source, sintered at 500-600°C for 2-4 hours, and crushed, and the particle size after crushing does not exceed 10 μm, and the carbon source is one or more of cyclodextrin, glucose, graphene, carbon nanotubes, fullerene, sucrose, starch, PEG, PVP, and citric acid.

Citation Information

Cited By

  • Method for preparing lithium manganese iron phosphate by recycling positive electrode material of waste lithium iron phosphate battery

    CN120553662A